Pengembangan Media Pembelajaran Matematika Berjudul Game Learn with Adventure Menggunakan Scratch - Anggi Lestari; Eyus Sudihartinih (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
The purpose of this study was to describe the result of developing mathematics learning media using the Scratch application entitled Game Learn with Adventure on the topic of the Linear Equation in One Variable (PLSV). This study uses the Multimedia Development Life Cycle (MDLC) development model through six-stage, namely concept, design, material collecting, assembly, testing, and distribution. Furthermore, a trial of the game was conducted on the participants, namely mathematics teacher prospective students. To find out the response of participants to the media that has been designed so that researchers provide a questionnaire on Google Form and interviews. Research participants are 20 of the Mathematics Education Study Program class of 2021 semester 2 at one of the universities in Bandung. Based on the research results, it is known that the game learn with adventure on the PLSV topic can be designed very well through the Scratch application in the MDLC development model. The results of the calculation of student responses show an average percentage of 93.3% of positive statements in the very good category. Thus the need for research to determine the effectiveness of the learning process and game development on different topics.